PENGARUH EKSPOR KOMODITI NON MIGAS TERHADAP PERTUMBUHAN EKONOMI PROPINSI SUMATERA BARAT - Yenni Del Rosa (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
This study aims to determine the effect of non-oil commodity exports to the economicgrowth of West Sumatra province in 2011 - 2015. The research data in the form of timeseries data collected from Bank Indonesia and the Central Bureau of Statistics. Theaverage economic growth of West Sumatra province for 5 years at 5.986% and theaverage value of non-oil commodity exports 2,032,112.8, the average volume of exportsof non-oil commodities 2,902,897.4 tons. Having performed classical assumption turnsout all research data is normal with JB test test for 3,814 < 27.587 at a significance levelof 5%, with a value not autocorrelation Durbin Watson heterokedastisitas 1,326 and doesnot occur with Gljser test for significant value 0.872 > 0.05. Simple linear regressionequation obtained Y = -5.609 + 2,341X + e where exports of non-oil commodities positiveeffect on the economic growth of West Sumatra province in 2011 - 2015. Based on thepartial test for significance level of 5% were non-oil commodity exports no significanteffect on growth West Sumatra provincial economy in 2011 - 2015. It can also be shownby R square value of 0.067 means that the economic growth of West Sumatra province in2011-2015 only affected by the non-oil commodity exports by 6.7% while the remaining93.3% is influenced by other factors which is not included in the research model.Keywords: non-oil commodity exports, economic growth